PURPLE SWEET POTATO BARS DENGAN PENAMBAHAN PISANG AMBON DAN KACANG HIJAU : EVALUASI SIFAT KIMIA, FISIK, DAN SENSORI Purple Sweet Potato Bars with Addition of Ambon Banana and Mung Beans: Evaluation of Chemical, Physical and Sensory Properties - Sussi Agustin, Dieffa; Astuti, Sussi; Sugiharto, Ribut; Nurdjanah, Siti (Jurusan Teknologi Hasil Pertanian, 2023)
The research aimed to obtain the formulation of additional ambon banana and mung beans in purple sweet potato bars with chemical, physical, and sensory properties that can accepted by consumers. The research was arranged in a Complete Randomized Block Design (CRBD) with nine treatments and three replications. Comparative treatment of ambon banana and mung beans consists of nine levels, namely F1 (10%:90%); F2 (20%:80%); F3 (30%:70%); F4 (40%:60%); F5 (50%:50%); F6 (60%:40%); F7 (70%:30%); F8 (80%:20%); and F9 (90%:10%). The data obtained were analyzed for the similarity of variance with the Bartlett test and the addition of the data tested by the Tuckey test; then, the data were analyzed by variance to determine the effect between treatments. If there is a significant effect, the data is further analyzed by Honestly Significant Difference (HSD) at the level of 5%. The results showed that the best purple sweet potato bars in the F6 treatment (60% ambon banana and 40% mung beans) were found. The best treatment of purple sweet potato bars (F6) produces moisture content of 16,88%, ash content of 2,84%, protein content of 5,72%, fat content 1,77%, crude fibre content 1,55%, and content carbohydrate 71,25%, calorical value 80,95 kkal/25 g equivalent to 97,24 kkal/30 g, water activity (aw) 0,83, and physical properties (texture) 0,85 kg.s/mm, aroma with a score of 3,58 (likes), taste with a score of 3,99 (likes), texture with a score of 3,71 (likes), and overall acceptance with a score of 3,75 (likes). Moisture content and water activity (aw) purple sweet potato bars with the addition of ambon banana and mung beans, all formulations compliant with standard Intermediate Moisture Food that is moisture content 10–40% and water activity (aw) 0,6–0,9.